Pengaruh Model Pembelajaran Contextual Teaching And Learning (CTL) terhadap Hasil Belajar Siswa pada Subtema III Pentingnya Menjaga Asupan Makanan Sehat Kelas V SD Negeri 124388 Siantar Martoba - Helena Desyka Dabukke; Minar Trisnawati Lumbantobing; Rio Parsaoran Napitupulu (Departement of Mathematics Education, 2023)
This research is motivated by the low learning outcomes of fifth grade students at SD Negeri 124388 Siantar Martoba. The contextual teaching learning (ctl) learning model on student learning outcomes in subtheme 3 The Importance of Maintaining Healthy Food Intake. The purpose of this study was to determine whether or not there was an influence of the contextual teaching learning (ctl) learning model on student learning outcomes in subtheme 3 of the importance of maintaining healthy food intake. The approach in this research is a quantitative approach. The results of testing the hypothesis using SPSS 22 assistance analysis. It is known that the results of tcount are 11,256. The ttable value in the statistical table with a significance of 0.05 with df n-2 is 325. Because tcount (11.256) > (325) the contextual teaching learning (CTL) model influences student learning outcomes. In conclusion, on student learning outcomes in subtheme 3 The Importance of Maintaining Healthy Food Intake.